The Impact Of Oyo & Treebo Hotel Brand Names On The Sales Of Unclassified Hotels Of New Delhi (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Tourism is one of the important sectors of India. Many of us travelling a lot especially in New Delhi.  Delhi is always a hot favourite travel spot from the ancient times. It was loved by all the emperors i.e. it has a lot of  monuments. This segment provides huge employment to our citizens. Each and every day, we have seen a new hotel  opening especially in budget segment. Budget segment is the segment in which hotel provides best customer satisfaction  in affordable prices. Objective: To check the impact of OYO & Treebo hotels brand names on the sales of unclassified  hotels of New Delhi. Methodology: In this study, the quantitative research method has been used. The data has been  taken from the hotel staff especially front office staff and hotel owner of Treebo & OYO hotels of New Delhi. Sample  was collected from Total 47 hotels. Questionnaire was used as a research tool to collect the data, and which was self administered by visiting the properties. Data was analyzed in overall basis and the results were presented in frequency  and percentage. Result: Majority of the hotels said that the overall sales & profit ratio is increased by these brands, and  the guest footfall is also increased due to the standards of these brands and they will be definitely a future of unclassified  hotels. Almost 86 % of hotels said that their profits are increased and agreed on the statement, that they are the future  of unclassified hotels. Conclusion: Overall experience of the guest is increasing, and it leads to great guest satisfaction  along with the great profits which are curbed by these hotels.
Keywords: Tourism; Unclassified; Economical; Budget; Hotel